Transcranial direct current stimulation for patients with walking difficulties caused by cerebral small vessel disease: a randomized controlled study - Xu, Qiaoqiao; Yin, Wenwen; Zhou, Xia; Wang, Shuo; Chen, Sishi; Yang, Jiajia; Xi, Chunhua; Sun, Zhongwu (Frontiers in Aging Neuroscience, 2025)
IntroductionCerebral small vessel disease (CSVD) is a chronic systemic degenerative disease affecting small blood vessels in the brain, leading to cognitive impairments. Transcranial direct current stimulation (tDCS), a non-invasive brain stimulation technique that applies low electrical currents to the scalp, shows promise in treating cognitive and movement disorders. However, further clinical evaluation is required to assess the long-term effects of tDCS on neuroplasticity and gait in patients with CSVD. We investigated the effects of long-term, repeated tDCS on local brain perfusion, network connectivity, cognition, and gait in patients with CSVD and gait disorders (CSVD-GD).MethodsThis prospective, single-blind, multicenter, randomized controlled study enrolled 66 patients with CSVD-GD, categorized into the tDCS and Sham groups. Imaging and gait characteristic data were collected over three periods using magnetic resonance imaging and a gait analyzer, along with neuropsychological assessments.ResultsAmong 156 volunteers with CSVD-GD, 66 participated in this study, with 60 completing the entire process. Compared to the Sham group, the tDCS group exhibited a more pronounced increase in the cerebral blood flow to the dural cerebrospinal fluid ratio in regions such as the orbitofrontal cortex and cingulate gyrus (P < 0.05, FDR corrected), along with significantly greater improvements in gait speed and stride length. Tolerance to tDCS was good, with no difference in adverse reactions between the groups, except for a scalp burning sensation reported during the 1st week (24.24% and 6.06% in the tDCS and Sham groups, respectively; P = 0.003).DiscussionLong-term tDCS is effective and safe for improving neuroplasticity and gait cognition in patients with CSVD.